Getting under the skin of the menopausal hot flush: a protocol to examine skin function and structure in symptomatic postmenopausal women - Roberts, Kirsty A.; Doyle, Abigail; Jones, Helen; Low, David A. (Frontiers in Global Women's Health, 2025)
IntroductionThe major pathophysiological symptom of the menopause affecting daily life is hot flushes, which are also associated with elevated cardiovascular disease risk. A hot flush is a sudden and intense heat sensation causing skin flushing and profuse sweating. Menopause-induced oestrogen deficiency could increase the sensitivity of skin blood vessels and sweat glands in postmenopausal women, which could result in more frequent and larger increases in skin blood flow in postmenopausal women consistent with hot flushes. Furthermore, oestrogen withdrawal could also alter the structure of the skin blood vessels and/or sweat glands which may also contribute to hot flushes. This trial aims to examine the function and structure of skin blood vessels and sweat glands in premenopausal and postmenopausal women.Methods and analysisThis is a single-centre multi-cohort observational study. Participants will attend the laboratory at Liverpool John Moores University (LJMU) on two separate occasions, ∼7 days apart. Visit 1 will consist of anthropometry, a blood sample and assessment of post-ganglionic skin blood vessel and sweat gland responsiveness via cutaneous microdialysis. At visit 2, participants will return for a skin punch biopsy. A between groups statistical analysis of the pre- and postmenopausal cohorts will be conducted in a blinded manner.Ethics and disseminationThe trial was approved by the North West - Greater Manchester South Research Ethics Committee (22/NW/0300) in the UK. The study adheres to The Declaration of Helsinki and is being conducted in accordance with the UK Policy Framework for Health and Social Care Research.DiscussionIdentifying functional and/or structural changes in skin blood vessels or sweat glands in women with hot flushes would increase our understanding of their cause(s) and side effects, and help to design effective treatments, including interventions that can manipulate the activity of the skin blood vessels and/or sweat glands via pharmacological or non-pharmacological methods. Trial registration numbersNCT06222073.